Land tenure security and luxury support plant species and trait diversity in urban community gardens - Philpott, Stacy M.; Bichier, Peter; Perez, Genesis; Jha, Shalene; Liere, Heidi; Lin, Brenda B. (Frontiers in Sustainable Food Systems, 2023)
Urban ecological communities are shaped by an array of environmental and physical factors that include climate, biogeography, species interactions, dispersal, and ecological filters at the habitat and landscape scales. In addition, in urban systems, many social dynamics, decision-making processes, and other social characteristics, such as development, policy, government actions, as well as socioeconomic status of residents – the so-called ‘luxury’ effect - may also play strong roles in shaping which species occur within the urban context. This interaction between ecological and social drivers may impact the species richness of communities, and may also influence their functional traits and functional diversity, with important implications for ecosystem services provided within urban spaces. Urban agroecosystems provide food and other well-being benefits to urban residents, and are valuable green spaces in the city that provide refuges for biodiversity. Despite this fact, one of the biggest risks to gardens is insecure land tenure. While plant communities within gardens may be shaped by gardener demographics, food cultures, and ecological processes, little is known about how factors such as luxury and land tenure security may impact plant diversity, plant functional traits, and functional diversity, as well as species and trait composition. In this study, we ask how garden physical features, luxury, and land tenure security influence plant species richness, functional diversity, and species and trait composition within gardens in the California central coast. We found that land tenure secure gardens had higher plant and crop richness. Variables associated with garden luxury boosted ornamental plant richness, flower abundance and height, lowered crop richness, and strongly impacted plant species composition. Garden plot size negatively correlated with plant species and functional richness and relative abundance of trees. Weed species richness was not impacted by any social or physical feature examined. Thus overall, in community gardens, cultivated plants, and their traits, are strongly shaped by the socioeconomic factors of land tenure security and luxury as well as the spatial distribution and size of garden plots, with important implications for both conservation and ecosystem services provided by garden habitats within cities.